PERJAMUAN KUDUS SEBAGAI SARANA ANUGERAH DAN IDENTITAS GEREJA DI ERA GLOBALISASI - Rikar Parenden; Kelpin Mendonga, Nirwana Wulandari, Yosita Sipapa’, Irawati (ADISAM PUBLISHER, 2025)
This article examines the Lord's Supper as a means of grace and church identity in the era of globalization. The Lord's Supper is not merely understood as a symbolic liturgical rite, but as a medium through which Christ presents the gift of salvation to the congregation. In the church's theological tradition, this sacrament serves as a means of renewing faith, strengthening the unity of the body of Christ, and affirming ecclesial identity. Amidst globalization marked by cultural pluralism, digital mobility, and the tide of relativism, the Lord's Supper serves as a reminder of the church's call to remain faithful to the Gospel while remaining open to the world. This article highlights four key dimensions: first, the Lord's Supper as a means of grace within the church's tradition; second, as an ecclesial identity that distinguishes the church from other social communities; third, as a means of psychological and social formation that strengthens congregational solidarity; and fourth, the adaptation of this sacrament to the digital age and the COVID-19 pandemic. Through qualitative analysis based on literature, this article confirms that the Lord's Supper has profound relevance for forming a faithful community, rooted in tradition, while also capable of facing global challenges with a clear identity and solid spirituality